2015
DOI: 10.1107/s2052252515012130
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of intermolecular interactions in orthorhombic rubrene

Abstract: A combination of single-crystal X-ray and neutron diffraction experiments are used to determine the electron density distribution in orthorhombic rubrene. The topology of electron density, NCI analysis and energetics of intermolecular interactions clearly demonstrate the presence of π⋯π stacking interactions in the crystalline state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
131
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(137 citation statements)
references
References 88 publications
(93 reference statements)
2
131
0
Order By: Relevance
“…The high values of mobility are attributed to the crystal packing which has a herringbone motif with a high overlap of the π‐conjugated tetracene backbone . In the monoclinic and triclinic polymorphs, device performance is significantly reduced due to the absence of π‐stacking interactions in the monoclinic polymorph and the significant slippage of tetracene backbones relative to one another in the triclinic polymorph . A comparative study on single crystals of the Cmca orthorhombic form and the triclinic form, both grown from solution, revealed that the orthorhombic form exhibited hole mobilities of up to 1.6 cm 2 V −1 s −1 , while the triclinic form showed lower charge carrier mobilities of only 0.1 cm 2 V −1 s −1 .…”
Section: Experimentally Observed Sipsmentioning
confidence: 99%
“…The high values of mobility are attributed to the crystal packing which has a herringbone motif with a high overlap of the π‐conjugated tetracene backbone . In the monoclinic and triclinic polymorphs, device performance is significantly reduced due to the absence of π‐stacking interactions in the monoclinic polymorph and the significant slippage of tetracene backbones relative to one another in the triclinic polymorph . A comparative study on single crystals of the Cmca orthorhombic form and the triclinic form, both grown from solution, revealed that the orthorhombic form exhibited hole mobilities of up to 1.6 cm 2 V −1 s −1 , while the triclinic form showed lower charge carrier mobilities of only 0.1 cm 2 V −1 s −1 .…”
Section: Experimentally Observed Sipsmentioning
confidence: 99%
“…The Hirshfeld surface analysis confirms the importance of H-atom contacts in establishing the packing. The large number of HÁ Á ÁH, HÁ Á ÁO/OÁ Á ÁH and HÁ Á ÁC/CÁ Á ÁH interactions suggest that van der Waals interactions and hydrogen bonding play the major roles in the crystal packing (Hathwar et al, 2015).…”
Section: Figurementioning
confidence: 99%
“…All of the contributions to the Hirshfeld surface are given in Table 3. The large number of HÁ Á ÁH, CÁ Á ÁH/HÁ Á ÁC and HÁ Á ÁBr/BrÁ Á ÁH interactions suggest that van der Waals interactions and hydrogen bonding play the major roles in the crystal packing (Hathwar et al, 2015).…”
Section: Figurementioning
confidence: 99%